Pelatihan Jurnalistik Digital Untuk Santri Mahasiswa Di Pesantren Mahasiswa An Najah Purwokerto - Rahman Rosyidi; Dwi, Andi; Setiawan, Ito (CV. Akira Java Bulu, 2025)
An-Najah Student Islamic Boarding School is an Islamic educational institution domiciled in Purwokerto, Central Java. Throughout its development, this Student Islamic Boarding School has strived to continuously innovate in providing learning for students that is relevant to the needs of the times. Specifically in terms of technology application, An Najah strives to improve students' skills in managing web-based information and education portals as a way for students to play an active role in cyberspace by disseminating useful information in accordance with Islamic values. In managing the portal as an information and education center, there are obstacles that urgently require immediate solutions. Portal managers, consisting of students who have been equipped with media development and content creation skills, face difficulties in creating portal content intensively and routinely. The difficulty lies more in how to find content ideas, inspiration, and then create content based on contemporary journalistic principles that suit the tastes of Generation Z. This difficulty impacts the long broadcast period of content due to constant changes and out-of-date content. As a solution, portal managers need to be equipped with knowledge of content creation and digital journalism skills through training activities. The digital journalism training aims to provide students with an understanding and skills in digital journalism, from news writing and content creation to managing social media as a means of preaching and education. This activity includes training, mentoring, and evaluation. The training is expected to enable portal managers to maintain the intensity of content distribution by creating content intensively and creatively based on the principles of digital journalism.